Tectonic Model of Bali Island Inferred from GPS Data - Cecep Sulaeman; Sri Hidayati; Amalfi Omang; Imam Catur Priambodo (Indonesian Journal on Geoscience, 2018)
DOI: 10.17014/ijog.5.1.81-91Seven periods of GPS campaign have been conducted for three years since March 2013 - October 2015 on fourteen GPS sites across Bali Island. The GAMIT/GLOBK 10.6 version was used to compute data with respect for thirteen reference sites of International Terrestrial Reference Frame (ITRF) 2008 surrounding Bali. The result shows that horizontal displacement varies between 1.93 and 22.53 mm/yr dominantly northeastward. Vertical displacement ranges at -184.34 to 33.79 mm/yr. The result of modeling using Coulomb 3.3 version indicates the deformation in Bali was mostly contributed by subduction at the southern part, West and East Flores Back-Arc Thrust at the north, Lombok Strait Fault and a fault at the eastern coast of Bali with the estimation maximum magnitude of 7.1, 6.6, 6.8, 5.8, and 5.2, respectively.